Kompetensi Pedagogik Guru Mata Pelajaran Ilmu Pengetahuan Sosial SMPN 2 Sidomulyo - Euis Rusmini; Pargito Pargito; pujiati pujiati (Faculty of Teacher Training and Education, University of Lampung, 2018)
The objective of this research is to describe pedagogical competence of teachers at SMPN 2 Sidomulyo. The study used qualitative method. The informants in this research are Social Studies teachers, school principal, and supervisor. The results of this study conclude that in general the pedagogical competence of teachers of IPS at SMPN 2 Sidomulyo good, and in particular: 1) teachers have good competence in mastery of the characteristics of learners, 2) teachers have good competence in mastery of learning theory and principles of learning that educate, 3) teachers have good competence in curriculum development, 4) teachers have o good competence in the design of learning activities that educate, 5) teachers have o good competence in the development of learners potentials, 6) teachers have o good competence in communication with learners, and 7) teachers have a fair competence in assessment and evaluation, and 8) The score of Social Students were good. pedagogic competence required advocacy, guidance, and intensive supervision, by both the principal and supervisor of IPS.Penelitian ini bertujuan untuk mendeskripsikan kompetensi pedagogik guru IPS di SMPN 2 Sidomulyo. Metode penelitian menggunakan metode kualitatif. Informan pada penelitian ini adalah guru IPS, kepala SMPN 2 Sidomulyo, dan pengawas. Hasil penelitian ini secara umum kompetensi pedagogik guru mata pelajaran IPS SMPN 2 Sidomulyo baik, dan secara khusus: 1) penguasaan karakteristik peserta didik cukup baik, 2) penguasaaan teori belajar dan prinsip‐prinsip pembelajaran yang mendidik baik, 3) pengembangan kurikulum baik, 4) perancangan kegiatan pembelajaran yang mendidik baik, 5) pengembangan potensi peserta didik kurang baik,6) komunikasi dengan peserta didik baik,7) penilaian dan evaluasi baik, serta 8) hasil belajar IPS siswa baik. Berdasarkan hasil penelitian ini, direkomendasikan bahwa untuk meningkatkan kompetensi pedagogik guru diperlukan advokasi, bimbingan, dan pengawasan yang intensif, baik oleh kepala sekolah maupun pengawas mata pelajaran IPS. Kata kunci : kompetensi,pedagogik, guru IPS